PELATIHAN IDENTIFIKASI KARANG HIAS BERBASIS SIMULASI DAN PRAKTIK LAPANGAN BAGI CALON ALUMNI DI TAMAN PENDIDIKAN LAUT BINTANG SAMUDERA, DESA SAWAPUDO, KABUPATEN KONAWE SULAWESI TENGGARA: PELATIHAN IDENTIFIKASI KARANG HIAS BERBASIS SIMULASI DAN PRAKTIK LAPANGAN BAGI CALON ALUMNI DI TAMAN PENDIDIKAN LAUT BINTANG SAMUDERA, DESA SAWAPUDO, KABUPATEN KONAWE SULAWESI TENGGARA - Wa Jali; Baru Sadarun; La Ode Muhammad Yasir Haya; Rahmadani; Fatmawati; Kamaruddin (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Coral identification is an important competency for marine science students because it supports ecosystem monitoring, coral reef conservation, restoration, and sustainable ornamental coral aquaculture. This community engagement activity aimed to provide students with knowledge and field experience in recognizing coral growth forms and visual characteristics with potential ornamental value. The activity was conducted at Bintang Samudera Marine Education Park, Sawapudo Village, through two main stages: a land-based coral identification simulation and direct field observation. The simulation included lectures, introduction to coral growth forms, identification sheets, photographic documentation techniques, and safety briefings. Field activities involved four diving teams, each consisting of four students, for a total of 16 student divers accompanied by diving assistants. Students without adequate diving skills conducted coral identification exercises in the intertidal zone under lecturer supervision. The participants observed and documented several coral morphotypes with potential ornamental value, particularly branching and tabular branching corals. The activity also stimulated students’ interest in coral transplantation, ornamental coral aquaculture, conservation, and marine entrepreneurship. Future activities should be conducted periodically and incorporate pre- and post-training assessments, standardized photographic catalogues, and coral growth monitoring to provide quantitative evidence of participants’ competency development.